Management of late-term pregnancy in midwifery- and obstetrician-led care - Kortekaas, Joep C. (BMC Pregnancy Childbirth, 2019)
ABSTRACT: Management of late-term pregnancy in midwifery- and obstetrician-led care. BACKGROUND: Since there is no consensus regarding the optimal management in late-term pregnancies (≥41.0 weeks), we explored the variety of management strategies in late-term pregnancy in the Netherlands to identify the magnitude of this variety and the attitude towards late-term pregnancy. METHODS: Two nationwide surveys amongst all midwifery practices (midwifery-led care) and all hospitals with an obstetric unit (obstetrician-led care) were performed with questions on timing, frequency and content of consultations/surveillance in late-term pregnancy and on timing of induction. Propositions about late-term pregnancy were assessed using Likert scale questions. RESULTS: The response rate was 40% (203/511) in midwifery-led care and 92% (80/87) in obstetrician-led care. All obstetric units made regional protocols with their collaborating midwifery practices about management in late-term pregnancy. Most midwifery-led care practices (93%) refer low-risk women at least once for consultation in obstetrician-led care in late-term pregnancy. The content of consultations varies among hospitals. Membrane sweeping is performed more in midwifery-led care compared to obstetrician-led care (90% vs 31%, p < 0.001). Consultation at 41 weeks should be standard care according to 47% of midwifery-led care practices and 83% of obstetrician-led care units (p < 0.001). Induction of labour at 41.0 weeks is offered less often to women in midwifery-led care in comparison to obstetrician-led care (3% vs 21%, p < 0.001). CONCLUSIONS: Substantial practice variation exists within and between midwifery-and obstetrician-led care in the Netherlands regarding timing, frequency and content of antenatal monitoring in late-term pregnancy and timing of labour induction. An evidence based interdisciplinary guideline will contribute to a higher level of uniformity in the management in late- term pregnancies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12884-019-2294-7) contains supplementary material, which is available to authorized users.